Legal Counselling on Bullying Prevention at State Elementary School Kowangan, Temanggung - Hakim, Hary Abdul; Dewi, Dyah Adriantini Sintha; Anjas, Rifai Riwandana; Listiani, Ria; Lahfa, Azzah Dzakiyyah; Sasmiyanti, Martia; Hartanto, Dimas Joko Periambodo (Borobudur Journal on Legal Services, 2025)
The aim of this program is to provide education on bullying and to raise collective awareness of the importance of creating a school environment free from violence. Bullying is a form of misconduct that frequently occurs in society and can also be found within school settings. The problem-solving strategy was implemented through a legal counseling approach combined with participatory, two-way discussions with the target participants at SD Negeri Kowangan. The target group consisted of 80 students from grades 3 to 6. The results of the program indicate a significant improvement in students’ understanding. By instilling legal awareness from an early age and conducting effective transformative socialization, the program successfully shaped students’ mindsets to be more empathetic and responsible in addressing bullying within the school environment.